Pengaruh Persepsi Harga, Kualitas Produk, dan Call to Action Terhadap Keputusan Pembelian Produk Kosmetik Hanasui Pada Generasi Z - Ariska Sari; Choirum Rindah Istiqaroh; Ahadiati Rohmatiah (Universitas Merdeka Madiun, 2025)
This study aims to analyze the influence of price perception, product quality, and call to action on purchasing decisions for Hanasui cosmetic products among Generation Z. Using a quantitative approach with a survey method, data were collected through questionnaires distributed to 100 respondents who are consumers of Hanasui cosmetic products from Generation Z, with data analysis using multiple linear regression and F test. The results showed that price perception did not have a significant effect on purchasing decisions with a p-value of 0.000 which was smaller than 0.05, while call to action also had a significant effect with a p-value of 0.036. Simultaneously, price perception, product quality, and call to action had a significant effect on purchasing decisions with a p-value of 0.000 and F count of 32.646 which was greater than F table 2.699. The conclusion of this study is that product quality and call to action are factors that have a significant effect on purchasing decisions for Hanasui cosmetic products among Generation Z, while price perception has no significant effect. Researchers suggest improving product quality and call to action strategies in marketing to attract further consumer interest.